Quasiclassical studies of Eley–Rideal and hot-atom reactions on a surface at 94K: H(D)→D(H)+Cu(111) - Vurdu, C. D.; Oezcelik, Süleyman; Guevenc, Z. B. (Elsevier BV, 2007)
Abstract Reactions and reaction dynamics of gas-phase H(or D) atoms with D(or H) atoms adsorbed onto a Cu(1 1 1) surface have been investigated by the quasi-classical molecular dynamics method. To simulate the H(D) → D(H) + Cu(1 1 1) system at a 94 K surface temperature, D(or H) adsorbates were disseminated arbitrarily on the surface of Cu(1 1 1) to form 0.50, 0.28 and 0.18 ML of coverages. The interaction of hydrogen atoms and the surface system is worked out by an LEPS function. LEPS parameters have been determined by using the total energy values which were calculated by a density functional theory (DFT) method and the generalized gradient approximation (GGA) for the exchange-correlation energy for various configurations of one and two hydrogen atoms on the Cu(1 1 1) surface. The Cu(1 1 1) surface, imitated by an embedded-atom method which is a many-body potential parameterized by Voter-Chen, is formed as a multilayer slab. The slab atoms are permitted to move. Various processes, trapping onto the surface, inelastic reflection of the incident projectile and penetration of the adsorbate or projectile atom into the slab, are examined. The dependence of these mechanisms on isotopic replacement has also been analyzed. Considerable contributions of the hot-atom pathways for the product formations are consequently observed. The rate of subsurface penetrations is obtained to be larger than the sticking rate onto the surface.